Starch-gel electrophoretic study of acid casein, rennin and alkaline milk phosphomomoesterase : a thesis presented to the Massey Agricultural College of Manawatu in partial fulfilment of the requirements of the degree of Master of Agricultural Science (Dairy Technology) - Aiyar, Krishna Ramachandran (Massey University, 1963)
In any electrophoretic method the mobility of an ion is directly proportional to the net charge carried by that ion. In a buffered system the charge on a protein molecule is dependent on the pH of the system and the protein type, as well as the type of buffer used(¹). Buffer ions may modify the charge on the protein molecule through combination with it and, hence, the latter need not necessarily have the same net charge in two different buffer systems of the same pH(¹,² ¹⁹). Smithies(³) was the first to develop the method of Horizontal Starch-Gel Electrophoresis in his study of bovine blood proteins. The raw material consisted of a high grade potato starch which had been partially hydrolysed by a 1:100 concentrated hydrochloric add acetone mixture at a temperature of 38.5°C for a suitable pre-determined time(³,⁴). For each new batch of potato starch pilot scale experiments must be run to determine the optimum hydrolysis time. Partial hydrolysis of the starch is done evidently to reduce the viscosity of the starch solution (³⁷,⁴⁰) to an optimum level. [From Introduction]
Keywords: Milk Analysis examination; Gel electrophoresis